A Metal‐Free Donor–Acceptor Covalent Organic Framework Photocatalyst for Visible‐Light‐Driven Reduction of CO2 with H2O. Issue 7 (5th March 2020) - Lei, Kai; Wang, Di; Ye, Liqun; Kou, Mingpu; Deng, Yu; Ma, Zhaoyu; Wang, Li; Kong, Yan
Abstract: Visible‐light‐driven CO2 reduction to valuable chemicals without sacrificial agents and cocatalysts remains challenging, especially for metal‐free photocatalytic systems. Herein, a novel donor–acceptor (D–A) covalent organic framework (CT‐COF) was constructed by the Schiff‐base reaction of carbazole‐triazine based D–A monomers and possessed a suitable energy band structure, strong visible‐light‐harvesting, and abundant nitrogen sites. CT‐COF as a metal‐free photocatalyst could reduce CO2 with gaseous H2 O to CO as the main carbonaceous product with approximately stoichiometric O2 evolution under visible‐light irradiation and without cocatalyst. The CO evolution rate (102.7 μmol g −1  h −1 ) was 68.5 times that of g‐C3 N4 under the same conditions. In situ Fourier‐transform (FT)IR analysis indicated that CT‐COF could adsorb and activate the CO2 and H2 O molecules and that COOH* species may be a key intermediate. DFT calculations suggested that nitrogen atoms in the triazine rings may be photocatalytically active sites. Abstract : Give and take : A carbazole‐based donor–acceptor covalent organic framework is used as a metal‐free photocatalyst for visible‐light‐driven reduction of CO2 with H2 O without cocatalysts, producing CO as the main carbonaceous product at a rate of 102.7 μmol g −1  h −1, along with an approximate stoichiometric O2 evolution. The CO evolution rate is 68.5 times that of g‐C3 N4, the most commonly reported metal‐free photocatalyst.